Bronchodilator responsiveness and dysanapsis in bronchopulmonary dysplasia. Issue 3 (4th July 2022) - Nelin, Leif D.; Kielt, Matthew J.; Jebbia, Maria; Jadcherla, Sudarshan; Shepherd, Edward G.
Background: The incidence of bronchopulmonary dysplasia (BPD) following preterm birth is increasing. Bronchodilators are often used to treat patients with BPD with little evidence to guide therapy. The aim of this study was to test the hypothesis that there are infant pulmonary function test (iPFT) parameters that can predict subsequent bronchodilator response in infants with BPD. Methods: Subjects in this study were part of a patient group in which we reported three BPD phenotypes (obstructive, restrictive and mixed) based on iPFT data. From that group, a cohort of 93 patients with iPFT data including bronchodilator response was eligible for this study. Results: Bronchodilator responsiveness was found in 59 people (63%) in the cohort. There were no differences in demographics between the responders and non-responders. There was no difference in forced vital capacity (FVC) between the two groups. Responders had significantly lower forced expiratory volume in 0.5 s (FEV0.5 ) and FEV0.5 /FVC (p<0.005) and greater indices of hyperinflation than did non-responders (p<0.005). Logistic regression modelling found that pre-bronchodilator FEV0.5 and functional residual capacity/total lung capacity were significantly associated with bronchodilator response. The magnitude of response to bronchodilators was negatively correlated (R= −0.49, R 2 = 0.24, p<0.001) with the FEV0.5 . The median dysanapsis ratio in responders (0.08, 95% CI 0.05–0.19) was significantly (p=0.005) smaller than in non-responders (0.18, 95% CI 0.06–0.38). Conclusion: These findings demonstrate that there are pulmonary function test parameters associated with bronchodilator response. Responders had evidence of greater dysanaptic lung growth than non-responders. In 93 BPD patients, 63% were responsive to bronchodilators and responders had significantly lower FEV0.5 and greater hyperinflation than did non-responders. The dysanapsis ratio in responders was significantly smaller than in non-responders. https://bit.ly/3yaWieK